2000
DOI: 10.1037/0735-7044.114.5.882
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of postrhinal and perirhinal cortex to contextual information processing.

Abstract: The role of the postrhinal cortex (POR) and the perirhinal cortex (PER) in processing relational or contextual information was examined with Pavlovian fear conditioning. Rats with electrolytic or neurotoxic lesions of the POR or PER were tested in 2 contextual fear conditioning paradigms. In Experiment 1, electrolytic lesions of the POR or PER produced impairments in contextual fear conditioning but not in conditioning to a phasic auditory conditioned stimulus. Neurotoxic lesions of the POR or PER likewise res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
154
2
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(178 citation statements)
references
References 34 publications
21
154
2
1
Order By: Relevance
“…Confirmation of these findings come from electrophysiological data which shows that there are different firing patterns observed in the perirhinal cortex during exposure to discontinuous tones compared to continuous tones (Furtak et al, 2007c) and from lesions of the perirhinal cortex where there is impairment of conditioning to ultrasonic vocalisations but not to continuous tones (Lindquist et al, 2004). These results fit with the data generated from recognition and fear conditioning tasks where the perirhinal cortex is required for processing more complex stimuli and contexts (Corodimas and LeDoux, 1995;Sacchetti et al, 1999;Bucci et al, 2000Bucci et al, , 2002Bussey et al, 2000;Eacott et al, 2001;Burwell et al, 2004a).…”
Section: The Role Of the Perirhinal Cortex In Fear Conditioningsupporting
confidence: 69%
See 2 more Smart Citations
“…Confirmation of these findings come from electrophysiological data which shows that there are different firing patterns observed in the perirhinal cortex during exposure to discontinuous tones compared to continuous tones (Furtak et al, 2007c) and from lesions of the perirhinal cortex where there is impairment of conditioning to ultrasonic vocalisations but not to continuous tones (Lindquist et al, 2004). These results fit with the data generated from recognition and fear conditioning tasks where the perirhinal cortex is required for processing more complex stimuli and contexts (Corodimas and LeDoux, 1995;Sacchetti et al, 1999;Bucci et al, 2000Bucci et al, , 2002Bussey et al, 2000;Eacott et al, 2001;Burwell et al, 2004a).…”
Section: The Role Of the Perirhinal Cortex In Fear Conditioningsupporting
confidence: 69%
“…Lesions of the rostral perirhinal cortex also lead to an attenuation of olfactory fear conditioning while sparing contextual fear conditioning Otto, 1997, 1998;Otto et al, 2000) and this sparing of contextual fear conditioning following perirhinal lesions has been confirmed by other groups (Phillips and LeDoux, 1995). However, other studies have shown that similar sized lesions in the same location (Corodimas and LeDoux, 1995) and larger ablations of the entire perirhinal cortex disrupt contextual fear conditioning (Sacchetti et al, 1999;Bucci et al, 2000Bucci et al, , 2002Burwell et al, 2004a). More generally temporary inactivation of the rostral perirhinal cortex seems to have an anxiolytic effect in an unconditioned fear task (Schulz-Klaus et al, 2005), this along with many of the above studies singling out the rostral region of the perirhinal cortex as being particularly important when it comes to emotional learning.…”
Section: The Role Of the Perirhinal Cortex In Fear Conditioningmentioning
confidence: 89%
See 1 more Smart Citation
“…This is because these cortices would not be available to support a context representation and the hippocampal formation would be deprived of the information it needs to make its contribution to contextual fear. The literature supports this analysis (Corodimas and LeDoux 1995;Buffalo et al 1999;Bucci et al 2000Bucci et al , 2002. Note this pattern of results, damage to these regions both before and after training impairs contextual fear conditioning differs from that associated with damage to the hippocampal formation because contextual fear conditioning is spared if the hippocampal formation is damaged before conditioning.…”
Section: Defining the Neocortical Systemsupporting
confidence: 67%
“…The perirhinal and postrhinal cortices are also implicated in contextual fear learning tasks, including contextual discrimination (Bucci et al, 2002), passive avoidance , and contextual fear conditioning (Corodimas and LeDoux, 1995;Sacchetti et al, 1999;Bucci et al, 2000; but see Phillips and LeDoux, 1995;Herzog and Otto, 1997). Such tasks are thought to require the processing of spatial information about the environment.…”
Section: Introductionmentioning
confidence: 99%